Theoretical and Methodological Basis of Fare System Management in Public Transport - SOKOL, Kateryna M.; STAMATIN, Oleksandr V.; SUKHONOS, Maria K.; LAHUNOVA, Iryna A.; MEDVEDCHUK, Oksana V. (Journal of Advanced Research in Law and Economics; Vol 10 No 8 (2019): JARLE Volume X Issue 8(46) Winter 2019DO - 10.14505/jarle.v10.8(46).29, 2019)
The research paper considers the issues of ensuring effective management of the processes of transformation of fare systems in public transport. Were analyzed the prospects for implementation of automated fare control systems and also the theoretical and methodological approaches to the formation of existing automated fare systems, which could determine the perspective of implementation of such systems in the domestic market of transport services provision, that can solve a number of problems related with fare simplicity and comfort, formation of a flexible fare system, use of various forms of payment, as well as monitoring and control of money revenues, including for transportation of preferential contingent. The analysis determined the cost-effectiveness of existing automated fare systems. Were predicted ways to improve the cost-effectiveness of existing automated fare systems through econometric modelling. The introduction of proposals after obtaining of simulation results will identify the potential economic impact and ways to optimize management processes. An analysis of the legal and regulatory framework for the formation and use of automated fare systems concluded that there was insufficient legislative support for the autonomy of management decisions on local public transport systems, in particular under the conditions of the reform of decentralization of power and the formation of integrated territorial communities. Have been developed proposals to improve the legal and regulatory framework for the automation of the management of fare systems in public transport. The analysis identified socio-economic aspects of the introduction of new approaches to the management of automated fare systems. Was developed an economic and mathematical model to manage automated fare systems in accordance with the conditions of the modern market and socio-economic challenges.